1996
DOI: 10.1111/j.1476-5381.1996.tb15669.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of vascular nitroglycerin tolerance by inhibition of protein kinase C

Abstract: We investigated whether in vivo inhibition of protein kinase C (PKC) can prevent the development of vascular tolerance and restore the sensitivity of isolated vessels to nitroglycerin (NTG). Tolerance was induced in male Wistar rats by a constant i.v. infusion of NTG 1 mg kg-' h'-, a dose which did not alter blood pressure. After 72 h, the aorta was removed and the sensitivity of aortic rings to NTG tested. Chronic NTG infusion resulted in a 5.5 fold decrease in NTG-sensitivity as compared with controls (vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…Our experiments, which showed that the combination of tempol and chelerythrine similarly reduced GTN tolerance, suggest that both agents are working through reduction of oxidant levels; tempol is scavenging superoxide and other ROS, and chelerythrine is reducing oxidant formation by preventing PKC activation. Our findings confirm previous reports of involvement of oxidative stress and PKC activity in GTN tolerance (Zierhut and Ball, 1996;Munzel et al, 2000). Our finding that O 2…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our experiments, which showed that the combination of tempol and chelerythrine similarly reduced GTN tolerance, suggest that both agents are working through reduction of oxidant levels; tempol is scavenging superoxide and other ROS, and chelerythrine is reducing oxidant formation by preventing PKC activation. Our findings confirm previous reports of involvement of oxidative stress and PKC activity in GTN tolerance (Zierhut and Ball, 1996;Munzel et al, 2000). Our finding that O 2…”
Section: Discussionsupporting
confidence: 93%
“…A previous study has reported that a protein kinase C (PKC) inhibitor can prevent tolerance to GTN (Zierhut and Ball, 1996). The PKC family includes at least 11 isozymes (Nishizuka, 1986).…”
mentioning
confidence: 99%
“…64 In addition, PKC-mediated phosphorylation causes inhibition of NOS, 65 and a recent report demonstrated that angiotensin II, via an ·O 2 Ϫ -and PKC-mediated mechanism, can trigger NOS uncoupling. 14 Inhibition of PKC prevented tolerance in a rat model, 66 but the effect of endothelin-1 receptor or PKC inhibition in the response to nitrates in humans has not yet been tested.…”
Section: Neurohormonal Activation and The Control Of ·O 2 ؊ Productionmentioning
confidence: 99%
“…Peroxynitrite, O2 -, or both might be responsible for the development of nitrate tolerance. 21 In addition, NTG is a potent stimulus for PKC activation in cultured endothelial cells, and inhibition of PKC prevents in vivo nitrate tolerance. 21 Because PKC activation is induced by O2 -and peroxynitrite, 22 NTG might initiate a vicious cycle that involves activation of PKC, increased O2 -and peroxynitrite, depletion of BH4, and uncoupling of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, NTG is a potent stimulus for PKC activation in cultured endothelial cells, and inhibition of PKC prevents in vivo nitrate tolerance. 21 Because PKC activation is induced by O2 -and peroxynitrite, 22 NTG might initiate a vicious cycle that involves activation of PKC, increased O2 -and peroxynitrite, depletion of BH4, and uncoupling of eNOS. NTG-induced increases in oxidative stress could also lead to increased production of endothelin-1 within endothelial and smooth muscle cells, leading to PKC activation, which in turn may trigger enhanced constrictor responses to almost every receptor-dependent agonist.…”
Section: Discussionmentioning
confidence: 99%